Redox homeostasis and metabolic profile in young female basketball players during in-season training - Militello, R.; Luti, S.; Parri, M.; Marzocchini, R.; Soldaini, R.; Modesti, A.; Modesti, P. A. (healthcare, 2021)
Background: Most studies on oxidative stress markers and antioxidant levels have been conducted in male athletes, although female participation in sport has increased rapidly in the past few decades. In particular, it could be important to assess oxidative stress markers in relation to the training load because the anaerobic path becomes predominant in high-intensity actions. Methods: Ten female professional basketball players, performing five 2 h-lasting training sessions per week, and 10 sedentary control women were investigated. Capillary blood and saliva samples were collected in the morning before the training session. The antioxidant capacity and the levels of reactive oxygen metabolites on plasma were determined measuring Reactive Oxygen Metabolite and Biological Antioxidant Potential (d-ROMs and the BAP Test). Salivary cortisol was detected by using commercial enzyme-linked immunosorbent assay kit. Results: The antioxidant capacity (BAP value) was significantly higher in elite basketball players (21.2%; p < 0.05). Conversely, cortisol (51%; p < 0.009) and the levels of oxidative species (d-ROM, 21.9%; p < 0.05) showed a significant decrease in elite athletes.